Meta-analysis of the prevalence of obstructive sleep apnea and associated risk factors among Parkinson’s disease - Aini, Nur; Putri, Alfiani Rahmi; Banda, Kondwani Joseph; Janitra, Fitria Endah (Sleep and biological rhythms, 2025)
Sleep disorders are the most distressing non-motor problems among Parkinson’s disease (PD), whereas obstructive sleep apnea (OSA) is a type of sleep disorder that commonly occurs in Parkinson’s disease. Therefore, we conducted this meta-analysis to estimate the prevalence of OSA in Parkinson’s disease. A comprehensive search in CINAHL, Embase, Ovid MEDLINE, PubMed, Scopus, and Web of Science, following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, was conducted from inception to September 2023 to identify studies on the prevalence of PD patients with OSA. A Comprehensive Meta-Analysis software version 3.0 and R software with random-effects models were used for pooled prevalence and prediction interval analysis. We assessed heterogeneity using I 2 test and Cochran’s Q-statistic and study quality with Hoy's risk of bias. Moreover, meta-regression and subgroup analysis identified factors contributing to prevalence. A total of 42 studies with 3342 participants were included. The pooled prevalence of OSA among Parkinson’s disease patients was 45% (95% CI: 39–52%). Based on 95% prediction interval, the future prevalence of OSA in PD was expected to vary from 13 to 83%. Moderator analyses showed that male sex, higher BMI, and country geographical area were significantly associated with OSA prevalence, in which South and North America are the top two continents that have a high prevalence of OSA. This study gives a comprehensive overview of the high prevalence of OSA and associated factors in Parkinson’s disease, which can be used for planning care and future research.